Síntesis de diagramas de radiación con agrupaciones circulares de antenas aplicables en sistemas umts 3g - Suárez Fajardo, Carlos Arturo; Ferrando Bataller, Miguel; Valero Nogueira, Alejandro; Poveda Zafra, José Noé (Ingeniería, 2001)
This article describes the synthesis of radiation patterns with circular antenna arrays using directive elements, applicable in the intelligent antennas systems (Smart Antennas) for the base station, like a viable solution in UMTS systems and in front of the new demands of the market. As a basic element of directive radiation pattern, the infinite filament of constant current will be used, in front of a metallic infinite cylinder whose results will be easily expandable to the case of finite dipoles in front of infinite metallic cylinder. The used technique will be that of Fourier, as article continuation Suárez - Ferrando [1] and a method for synthesizing the radiation pattern with antenna array of N infinite filament of constant current uniformly disposed around a circular ring an in front of a cylinder is proposed. The required excitation currents are determined from a deduced formula in the paper.